MENINGKATKAN KEMAMPUAN MENULIS KALIMAT SEDERHANA MELALUI MODEL SNOWBALL THROWING DI KELAS II SDN 11 LIMBOTO BARAT KABUPATEN GORONTALO - Evi Hasim; Indah Permatasari Lamusu (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2021)
Indah Permatasari Lamusu. 2021,Improving students' Ability in Writing simple sentences using the snowball throwingmodel in the 2nd grade of SDN 11 Limboto Barat, Gorontalo District. undergraduate thesis. Department of elementary teacher education, faculty of education, state university of gorontalo.the principal supervisior is Dra. Evi Hasim, M.Pd and the Co Supervisior is Dr. Wiwy T. Pulukadang, S.Pd, M.Pd The research problem is whether or not the snowball throwing model can improve students' ability in writing simple sentences in the 2nd grade of SDN 11Limboto Barat, Gorontalo District. the objective is to improve the students' ability in writing simple sentences using the snowball throwing model in the 2nd grade of SDN 11 Limboto Barat, Gorontalo District. This research is a classroom action research comprising 2 cycles.